Functional mapping of microRNA promoters with dCas9 fused to transcriptional regulators - Kumar, Pradeep; Courtes, Mathilde; Lemmers, Céline; Le Digarcher, Anne; Coku, Ilda; Monteil, Arnaud; Hong, Charles; Varrault, Annie; Liu, Runhua; Wang, Lizhong; Bouschet, Tristan (Frontiers in Genetics, 2023)
MicroRNAs are small non-coding RNAs that control gene expression during development, physiology, and disease. Transcription is a key factor in microRNA abundance and tissue-specific expression. Many databases predict the location of microRNA transcription start sites and promoters. However, these candidate regions require functional validation. Here, dCas9 fused to transcriptional activators or repressors - CRISPR activation (CRISPRa) and inhibition (CRISPRi)- were targeted to the candidate promoters of two intronic microRNAs, mmu-miR-335 and hsa-miR-3662, including the promoters of their respective host genes Mest and HBS1L. We report that in mouse embryonic stem cells and brain organoids, miR-335 was downregulated upon CRISPRi of its host gene Mest. Reciprocally, CRISPRa of Mest promoter upregulated miR-335. By contrast, CRISPRa of the predicted miR-335-specific promoter (located in an intron of Mest) did not affect miR-335 levels. Thus, the expression of miR-335 only depends on the promoter activity of its host gene Mest. By contrast, miR-3662 was CRISPR activatable both by the promoter of its host gene HBS1L and an intronic sequence in HEK-293T cells. Thus, CRISPRa and CRISPRi are powerful tools to evaluate the relevance of endogenous regulatory sequences involved in microRNA transcription in defined cell types.